Development through Knowledge Economy: Cluj-Napoca – a European Smart City - PORUMB, Elena Marilena; IVANOVA, Nadia Valentina (Management Dynamics in the Knowledge Economy, 2014)
The paper is related to both theoretical concepts and best practice in the field of Knowledge Management Strategy. We have designed a mixture of research methodology that covers literature review, comparative case-study analysis, and best practices in the Smart-City field, in order to propose an adequate model, with a suitable quick guide for implementation that may provide a solution for the development of Cluj-Napoca case study. After an in-depth literature review, we proposed the following as the main research question: Could a smart city comparative case study methodology be used as a knowledge management strategy for development? After a preparatory stage we focused on the upgrading of a smart city development model. To put this model at work we looked for and designed a quick guide that can be used as a tool for implementing the model named Knowledge Broker Intervention Model (KBIM). This KBIM and the quick guide for implementation may be seen as our small contribution to the theory and practice in the field. The Knowledge Broker Intervention Model was designed to improve the networks of components in a new way and a more sustainable development. These outcomes of the comparative analysis may be used as a starting point for the transformation of Cluj Napoca into a Smart City based on the quick guide we developed. Cluj Innovation City is a first step towards transforming Cluj-Napoca into a Smart City, which could be developed around the existing Cluj IT Cluster. The role of a knowledge broker would be to ensure that knowledge of the organizational culture of private firms could be harvested, processed and further transferred to universities. In their turn, universities would adopt the new knowledge and apply it in such a way in which it will influence the nurture of scientists. This would come as a solution in the process of closing the gap between knowledge generation, dissemination and feedback actions. It will link research results with policy and practice, as well as match some research portfolios to the needs of policy and practice, therefore the knowledge broker would act as a catalyst in this scenario.